Hormone use among Nepali transgender women: a qualitative study - Pramod R Regmi; Edwin van Teijlingen; Sanjeev Raj Neupane; Sujan Babu Marahatta (BMJ Open)
Objectives There is a dearth of information on transgender individuals in Nepal, particularly studies exploring their use of hormone therapies. The objectives of this study therefore were to explore (1) how hormones are used, (2) types of hormones used and (3) side effects experienced by transgender women after hormone use. This is the first study of its kind in Nepal addressing this important public health issue.Setting The study was conducted in four districts of Nepal: Kathmandu, Sunsai, Banke and Kaski.Design and participants This qualitative study comprises eight focus group discussions (FGDs) and nine interviews. FGDs and three face-to-face interviews were held with transgender women aged 18 years and older and six interviews with stakeholders working with and advocating on behalf of this population. The study was conducted between September 2016 and March 2017.Results Our participants were young. The majority of FGD participants had completed school-level education and 40% had been using hormones for 1 to 3 years. Five overlapping themes were identified: (1) reasons and motivations for hormone use; (2) accessibility and use of hormones; (3) side effects; (4) utilisation of healthcare services and (5) discontinuation of hormone use.Conclusion Hormone use was common in our sample. Most received information on hormone therapy online and through their peer networks. A few study participants sought doctors’ prescriptions for hormone therapy, but hormones were more likely to be bought from local private pharmacies or abroad through friends. This kind of self-medication is associated with a range of risks to the physical and mental health of transgender individuals. Incorporating information, education and communication about hormone therapy into existing health promotion interventions targeted to this population may help transgender people to make better informed choices.